The potential of space geomatics engineering applications in transportation analysis and planning - Mahmoud M.S. Albattah; Salah Edin Youssef (Egyptian Journal of Remote Sensing and Space Sciences, 2021)
Megapoleses in developing countries, are subject to persistent increase in road traffic due to immigration, increase in prosperity, fast development expansion of economy, travel and tourism. Road traffic congestion is increasing exponentially while road infrastructure are not and cannot be increased in the same ratio.The present study proposes the exploration of the potential of Satellite Imagery, GIS and traffic flow information in solving traffic congestion in one of these cities in developing countries.The Land-use has been generated from a combination of the imagery of the Landsat and SPOT.A Digital Terrain Model (DTM) was extracted from a large-scale Stereo-pair of aerial photographs with a geometric resolution of 60 cm.Up-to-date information such Land use, DTM, Access site information and Restricted Access Area information were combined in a GIS for analysis and visualization.Analytic Hierarchy Process is used for obtaining the optimal alternatives to the congested roads.